2009
DOI: 10.1038/nrurol.2009.126
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction following prostatectomy: prevention and treatment

Abstract: Radical prostatectomy (RP) remains the standard treatment for men with clinically localized prostate cancer, despite the range of alternative treatment modalities. Even with significant advances in surgical technique and superb results for cancer control and preservation of urinary function, erectile dysfunction (ED) following RP is a common complication. This is mainly attributed to temporary cavernous nerve damage (neuropraxia) resulting in penile hypoxia, smooth muscle apoptosis, fibrosis and veno-occlusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 95 publications
(97 reference statements)
0
64
0
Order By: Relevance
“…Patient selection and surgical technique are the major determinants of post-operative erectile function (2). The shift from open to laparoscopic surgery represented a completely new experience for surgeons, who were exposed to surgical anatomy through a different perspective and were required to learn new surgical procedures and to deal with new surgical tools (2).…”
Section: Introductionmentioning
confidence: 99%
“…Patient selection and surgical technique are the major determinants of post-operative erectile function (2). The shift from open to laparoscopic surgery represented a completely new experience for surgeons, who were exposed to surgical anatomy through a different perspective and were required to learn new surgical procedures and to deal with new surgical tools (2).…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of better nerve-sparing on improving early urinary outcomes after RP in previously potent men have been suggested in the literature, [10][11][12] it has not been shown that early PDE5i use after RP may adversely affect early urinary health-related quality of life. It is known that PDE5i therapy improves erections during the convalescence from nerve-sparing RP; 13 its effects on penile rehabilitation with daily use after RP are less clear. A number of RCTs have reported on the effects of daily PDE5i use on postoperative erectile function with discordant results.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this treatment is the high, virtually immediate effectiveness of the drug in terms of erectile function and especially of hardness, a factor often considered critical to patient satisfaction [ 9,10 ] . In fact, even after nerve-sparing RP, neuroapraxia involves a period of functional insuffi ciency of nerve fi bres of up to 24 months, limiting the effectiveness of the use of PDE-5 inhibitors [ 11,12 ] .…”
Section: Discussionmentioning
confidence: 99%